2021
DOI: 10.1259/bjro.20210055
|View full text |Cite
|
Sign up to set email alerts
|

CT findings in sequel of COVID-19 pneumonia and its complications

Abstract: A significant number of patients after initial recovery from COVID-19 continue to experience lingering symptoms of the disease that may last for weeks or even months. Lungs being the most commonly affected organ by COVID-19, bear the major brunt of the disease and thus it is imperative to be aware of the evolution of the pulmonary parenchymal changes over time. CT chest is the imaging modality of choice to evaluate post-COVID lungs. Persistent ground-glass opacities, septal thickening and parenchymal bands, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…Atypical findings that were observed in our study include tree in bud opacities, "halo" sign, "Reverse halo" sign, and cavitation. These findings are in concordance with the previous studies published by Garg et al describing the pulmonary sequelae in COVID-19 patients in which they concluded that COVID-19 patients are more prone to develop superadded bacterial and fungal infections secondary to immunosuppression [16]. Similar to their results, two of our patients were found to have COVID Associated Pulmonary Mucormycosis and one patients had COVID associated Pulmonary Aspergillosis; while another two patients found to have spontaneous pneumomediastinum and four patients had pneumothorax which is in agreement with the previous reports published by Brogna et al [17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Atypical findings that were observed in our study include tree in bud opacities, "halo" sign, "Reverse halo" sign, and cavitation. These findings are in concordance with the previous studies published by Garg et al describing the pulmonary sequelae in COVID-19 patients in which they concluded that COVID-19 patients are more prone to develop superadded bacterial and fungal infections secondary to immunosuppression [16]. Similar to their results, two of our patients were found to have COVID Associated Pulmonary Mucormycosis and one patients had COVID associated Pulmonary Aspergillosis; while another two patients found to have spontaneous pneumomediastinum and four patients had pneumothorax which is in agreement with the previous reports published by Brogna et al [17].…”
Section: Discussionsupporting
confidence: 93%
“…The mean (±SD) CT severity score in our study population was 16.10±7.95. The median (IQR) CT severity score was 19 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Ct Imaging Characteristicsmentioning
confidence: 99%
“…Однако не удалось доказать связь с каким-то конкретным бактериальным или грибковым возбудителем, поскольку этот симптом при КТ обнаруживался у 100% пациентов с любой сопутствующей респираторной инфекцией. Таким образом, несмотря на наличие новых участков консолидации, полостных образований и бронхоэктазов, обычно свидетельствующих о наличии грибковых инфекций, следует учитывать, что и они не являются пато гномоничными [4,45].…”
Section: кт-признаки Covid-19 ассоциированного аспергиллеза легкихunclassified
“…Согласно опубликованным данным, у пациентов с COVID-19 признаки бронхиолита, которые проявляются утолщением стенок бронхов и/или появлением внутридольковых очагов и симптома "дерева с набухшими почками", являются признаками аспергиллеза дыхательных путей [56]. Так, наличие групп центрилобулярных очагов, перибронхиальных консолидаций и утолщения стенок бронхов может ассоциироваться с COVID-АЛ [45]. По наблюдениям E. Baratella и соавт., только у 1/ 9 пациентов с COVID-АЛ была "классическая" лучевая картина грибкового поражения в виде полостей или диффузных паренхиматозных узелков.…”
Section: кт-признаки Covid-19 ассоциированного аспергиллеза легкихunclassified
“… 11 In addition, notable CT finding of pulmonary artery pseudoaneurysm has been reported in patients of pulmonary mucormycosis, both in cases with or without comorbid COVID-19. 12 , 14 …”
Section: Covid-19–associated Pulmonary Mucormycosismentioning
confidence: 99%